Immature stages of the Rubiaceae-feeding metalmark butterflies (Lepidoptera: Riodinidae), and a new function for the tentacle nectary organs - Nielsen, Gregory J.; Kaminski, Lucas A. (Zootaxa, 2018)
Metalmark butterfly (Riodinidae) diversity is heavily concentrated in the Neotropical lowland forests but despite their prevalence basic information on immature stages is still scarce. Here we describe the life cycle of seven taxa in the Rubiaceae-feeding section of the Mesosemiina, including three Mesosemia Hübner, [1819], three Leucochimona Stichel, 1909, and the first information for Semomesia Westwood, 1851. Immature stage morphology of Mesosemia cippus Hewitson, 1859 is described in detail through scanning electron microscopy. Generally, eggs are laid singly and caterpillars are folivorous with a cryptic green coloration except for M. cippus which has gregarious caterpillars with a bright yellow color pattern. Immature stages of all analyzed species are morphologically similar and characterized by: oblate spheroid eggs with small spines on the rib intersections; nonmyrmecophilous larvae with sparse long setae on chalazae or pinnacles, perforated cupola organs (PCOs) and tentacle nectary organs (TNOs) in all instars; pupae attached longitudinally to the substrate by the cremaster and a silk girdle that crosses over abdominal segments A1 or A2. Functionality of the TNOs is documented for the first time in the “Mesosemia section” of the Mesosemiina, but they are not used to facilitate symbiotic interactions between caterpillars and ants. When molested, caterpillars everted the TNOs secreting a conspicuous drop of opaque and viscous liquid with a defensive function. A summary of the host plants in the “Mesosemia section” is presented, confirming the preponderance of oligophagy in the Rubiaceae. The morphological and behavioral traits here described are discussed in the context of defense against natural enemies and constitute key information to understanding the evolution of ant-organs and myrmecophily in riodinids.